Chromosome in situ suppression hybridisation in clinical cytogenetics. - Hulten, M A (1991)
The use of chromosome in situ suppression hybridisation with whole chromosome libraries has previously been reported by various research laboratories to be an effective method of identifying specific human chromosomal material. As a clinical cytogenetic service laboratory we have used the technique as a complement to diagnosis by classical chromosome banding. In three examples of structural rearrangements the potential use of the 'chromosome painting' method is assessed for its ability to enhance the routine cytogenetic service currently available.